Hiperventilación y su influencia en el traumatismo craneoencefálico en pacientes de 15 a 60 años de la unidad de cuidados intensivos clínica sur hospital Guayaquil primer semestre 2018 - Carvajal Tovar, Hamilton Adan (2018)
Cranioencephalic trauma (CET) is a physical and direct injury to cranial structures in the brain and meninges that have serious neurological consequences. This lesion frequently constitutes morbidity and mortality in the adult population. The objective of this study is to determine how hyperventilation affects patients with traumatic brain injury subjected to mechanical ventilation, thus establishing all the positive and negative factors that affect TCE patients at the time of this strategy. The methodology used to achieve the goals proposed in this research is based on the descriptive, analytical and deductive method which allowed us to address all the problems under study, collect the data and establish the results and conclusions of this project. The present investigation generates a great importance in the health area, since it is directed to the professionals that work in the area of Intensive Care Unit (ICU) in order to reinforce the knowledge about the influence exerted by hyperventilation in the evolution of patients with TBI and thus contribute to the prevention of complications.